APPLICATION OF SIMPLE INHALATION THERAPY IN PULMONARY TB PATIENTS TO OVERCOME THE INEFECTIVENESS OF BREATH WAY CLEANING - Putri, Dini Firdiana; Soleha, Umdatus; Firdaus; Putri, Rahmadaniar Aditya (Universitas Nahdlatul Ulama Surabaya, 2023)
Background: Inadequate airway clearance is one of the nursing issues that arises during the pulmonary tuberculosis disease process. If untreated, ineffective airway clearance can result in hypoxemia, decreased consciousness, and even cell death. Objective: The purpose of this study is to see that simple inhalation therapy can help pulmonary tuberculosis patients at the Banyu Urip Community Health Center to overcome ineffective airway clearance. Methods: The research methodology combines a case study approach with a family nursing process approach, with one case as the unit of analysis, Mrs. K, a pulmonary tuberculosis patient who get treatment at the Banyu Urip Community Health Center working area. Data was gathered through interviews, physical examinations, supporting examinations, and a literature review. In the study, 350 ml of hot water steam and 5 drops of eucalyptus oil were applied twice a day for three days, for 10-15 minutes. Result: The research results of simple inhalation therapy proved to have a positive effect on Mrs. K, as evidenced by a reduction in verbal complaints, including ease in driving out secretions, respiratory frequency was within normal limits, and breathing became easier, because the cineol content of eucalyptus oil has mucolytic, bronchodilator, and anti-inflammatory functions. Conclusion: To overcome airway ineffectiveness and improve health status, simple inhalation therapy combined with eucalyptus oil can be used as an alternative. Non-pharmacological techniques that are simple, easy to use but provide numerous benefits in health care facilities, such as simple inhalation therapy, are expected of health care workers.